Empowering SMEs through Generative AI: Opportunities, Challenges, and Strategic Implications for Sustainable Innovation - BRAN, Florina; BODISLAV, Dumitru Alexandru; CĂLIN, Ana Maria; MĂNESCU, Andreea Maria (European Journal of Sustainable Development, 2025)
Generative Artificial Intelligence (AI) is revolutionizing the competitive environment for small and medium-sized enterprises (SMEs) by improving market adaptability, innovation, and productivity. The transformative impact of generative AI on SMEs is the primary focus of this paper, with a particular emphasis on its function in content creation, customer engagement, automation, and decision-making. The adoption of AI has been historically dominated by large corporations. However, the accessibility of generative AI tools has allowed small and medium-sized enterprises (SMEs) to compete in global markets, optimize resource allocation, and surmount technological gaps. Nevertheless, the widespread adoption of this technology is significantly impeded by obstacles such as data privacy concerns, ethical considerations, and integration costs. This study investigates the ways in which generative AI is utilized by SMEs to drive business growth, identifies sector-specific advantages, and discusses the policy implications through empirical analysis and case studies. The results emphasize that, although generative AI democratizes access to advanced technology, its long-term benefits for SMEs are contingent upon strategic implementation, regulatory frameworks, and digital literacy. This paper concludes with suggestions for policymakers, business leaders, and technology developers to guarantee that generative AI promotes sustainable innovation in the small and medium-sized enterprise sector. Keywords: Generative Artificial Intelligence, Small and Medium-Sized Enterprises, business innovation, digital transformation